Sources of variation in some of the reproductive traits of Gir cows - BHADORIA, H B S; KHAN, F H; TOMAR, S S; YADAV, M C (The Indian Journal of Animal Sciences, 2014)
Records on age at first conception, age at first calving, service period and calving interval of Gir cows maintained at the Kasturba Gandhi National Memorial Trust Dairy Farm, Kasturbagram, Indore, were analysed. The least squares means for age at first conception, age at first calving, service period and calving interval were 1442.81± 18.50, 1719.09±8.11, 138.93±5.53 and 439.02 ±5.98 days with coefficients of variation as 20.0, 17.0,67.0 and 26.0%, respectively. The effect of period on all the 4 reproductive traits was significant, but season did not influence any of the traits significantly. Significant differences in service period and calving interval were observed due to parity, the primiparous having significantly longer service period and calving interval as compared to pluriparous. The heritability estimates of age at first conception, age at first calving, service period and calving interval were 0.62±0.06, 0.68±0.07, 0.49±0.09 and 0.45±0.03, respectively. The higher estimates of heritability suggested possibility of genetic improvement in these traits by individual selection